Transient liquid-phase bonded 3D woven Ni-based superalloys. (November 2015) - Erdeniz, Dinc; Sharp, Keith W.; Dunand, David C.
Graphical abstract: Abstract: Architectured Ni-based superalloy scaffolds were fabricated by three-dimensional weaving of ductile Ni–20Cr (wt.%) wires followed by gas-phase alloying with aluminum and titanium via pack cementation. Bonding of neighboring wires occurs at necks that are formed by solid-state diffusion or by formation of a transient-liquid phase. Three-point bending tests of the superalloy weaves, after homogenization and aging to achieve a γ / γ ′ structure, show that, as bonding between wires increases, the materials withstand higher stresses and strains before onset of damage.